Plasmalogen-Based Liquid Crystalline Multiphase Structures Involving Docosapentaenoyl Derivatives Inspired by Biological Cubic Membranes - Angelova, Angelina; Angelov, Borislav; Drechsler, Markus; Bizien, Thomas; Gorshkova, Yulia E.; Deng, Yuru (Frontiers in Cell and Developmental Biology, 2021)
Structural properties of plasmenyl-glycerophospholipids (plasmalogens) have been scarcely studied for plasmalogens with long polyunsaturated fatty acid (PUFA) chains, despite of their significance for the organization and functions of the cellular membranes. Elaboration of supramolecular assemblies involving PUFA-chain plasmalogens in nanostructured mixtures with lyotropic lipids may accelerate the development of nanomedicines for certain severe pathologies (e.g. peroxisomal disorders, cardiometabolic impairments, and neurodegenerative Alzheimer’s and Parkinson’s diseases). Here we investigate the spontaneous self-assembly of bioinspired, custom-produced docosapentaenoyl (DPA) plasmenyl (ether) and ester phospholipids in aqueous environment (pH 7) by synchrotron small-angle X-ray scattering (SAXS) and cryogenic transmission electron microscopy (cryo-TEM). A coexistence of a liquid crystalline primitive cubic Im3m phase and an inverted hexagonal (HII) phase is observed for the DPA-ethanolamine plasmalogen (C16:1p-22:5n6 PE) derivative. A double diamond cubic Pn3m phase is formed in mixed assemblies of the phosphoethanolamine plasmalogen (C16:1p-22:5n6 PE) and monoolein (MO), whereas a coexistence of cubic and lamellar liquid crystalline phases is established for the DPA-plasmenyl phosphocholine (C16:1p-22:5n6 PC)/MO mixture at ambient temperature. The DPA-diacyl phosphoinositol (22:5n6-22:5n6 PI) ester lipid displays a propensity for a lamellar phase formation. Double membrane vesicles and multilamellar onion topologies with inhomogeneous distribution of interfacial curvature are formed upon incorporation of the phosphoethanolamine plasmalogen (C16:1p-22:5n6 PE) into dioleoylphosphocholine (DOPC) bilayers. Nanoparticulate formulations of plasmalogen-loaded cubosomes, hexosomes, and various multiphase cubosome- and hexosome-derived architectures and mixed type nano-objects (e.g. oil droplet-embedding vesicles or core-shell particles with soft corona) are produced with PUFA-chain phospholipids and lipophilic antioxidant-containing membrane compositions that are characterized by synchrotron SAXS and cryo-TEM imaging. The obtained multiphase nanostructures reflect the changes in the membrane curvature induced by the inclusion of DPA-based phosphoethanolamine (PE) and phosphocholine (PC) plasmalogens, as well as DPA-phosphoinositol (PI) ester derivative, and open new opportunities for exploration of these bioinspired nanoassemblies.